MOSQUE-BASED COMMUNITY DEVELOPMENT - Sutanto, Romi Wilham (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2019)
The subject of this research is how to develop a mosque-based community towards social, educational and economic services at the Nurul Islam Islamic Center Mosque in Bekasi City. The type of research used in this research is qualitative. Qualitative research is research that intends to understand the phenomenon of what the research subjects experience holistically in a descriptive way in the form of words and language, in a special natural context by utilizing natural methods. The results of this study concluded that the Nurul Islam Islamic Center Mosque in Bekasi City serves and organizes all social services and programs for the community. Such as serving the implementation of mass circumcision, donating for Orphans and Dhuafa, providing and carrying out sacrificial animal slaughter, serving the care of corpses, serving the receipt of zakat, infaq, and shodaqoh. By accommodating all aspirations, orienting the results in carrying out worship and social activities, paying attention to the interests of the congregation and holding the mandate and responsibility for implementation through the vision and mission that have been implemented. In addition to social services, the Nurul Islam Islamic Center Mosque in Bekasi City is able to foster and serve educational programs, through TPQ education, Tahfidzul Qur'an Institution, routine recitation of the Taklim Council, Youth Recitation, Recitation of Women, Recitation of Fathers and Monthly Recitation. Then the last mosque Nurul Islam Islamic Center Bekasi City has a community development program in the economic field, such as Baitul Maal, zakat house, and others. Even the Nurul Islam Islamic Center Mosque in Bekasi City has also developed and fostered MSME players for the advancement of the Muslim economy.